(untitled) (Nóema, 2019)
This paper aims to highlight the necessary and essential relation connecting the concepts of Praxis, Matter and Destiny in the context of Jean-Paul Sartre’s Critique of Dialectical Reason (first and second book). In order to approach such co-originality, I analyze the term “constitution” not as a static description but as the dynamic sense of the History, according to its specifical motility: the wandering.